Comparative Analysis of the Amount of Fuel Use for Main Motor 1 in Theory and Reality in the Field During Operation One Trip at KMN. Cahaya Lapawawoi 01 - Ade Hermawan; Teguh Binardi; Agustiawan Agustiawan; Samsi Samsi; Priyantini Dewi; Sobri Sobri; Istianto Budhi Rahardja (Journal of Applied Sciences and Advanced Technology, 2021)
Ships are units used for transportation, logistics industry, fishing units and so on. In its operations, ships use fuel oil to move and reach their intended destination. The fuel oil used includes heavy fuel oil (HFO), medium fuel oil (MFO), and intermediate fuel oil (IFO). The main factors that affect the high and low use of fuel are rotation (rpm) and also the operating time of the main engine. Flowmeter is a measuring tool to determine the amount of fuel oil consumption in the engine. The function of the flowmeter is to measure the volume of liquid that passes through the device so that the total volume of liquid that enters a container / place or machine is obtained. Flowmeter and Tachometer are very helpful in calculating fuel consumption on board. Basically, with the use of high rotation, it can accelerate the speed of the ship's movement to reach its destination.